Music - Ardley, Neil.; Dowell, Philip; Dunning, Mike; King, Dave (New York : Dorling Kindersley, 2000)
Text and pictures introduce musical instruments from early times to the present--from pipes and flutes to electronic synthesizers.
Includes index.
Wilson's Children.
6.8.
6.8
5-8
Keywords: Musical instruments -- Juvenile literature; Musical instruments -- Pictorial works -- Juvenile literature; Musical instruments; Musical instruments -- Pictorial works; Music; Musical instruments; Musical instruments -- Pictorial works